Bland-Altman-Plots for the difference between App and 24-hour-recall on Days 1, 2, 3 and the mean over the three days for ‘Vegetables and salad’. - Jette Hinrichsen (22683252) (2025)
Bland-Altman-Plots for the difference between App and 24-hour-recall on Days 1, 2, 3 and the mean over the three days for ‘Vegetables and salad’.